KAJIAN ASINONIMITAS AL-KITAB WAL AL-QURâ€™AN: QIRAâ€™AH MUASHIRAH - Elkarimah, Mia Fitriah (LINGUA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2017)
Â This researchÂ  describes the concept of Muhammad Syahrur on the birth of asynonymous theory, the ignorance of synonymous in the Qur'an.Â  Synonymous in the Qur'an is frequently discussed, but debates appear where Syahrur is in disagreement. This research used qualitative approach and content analysis as the design.Â  The source of Â data was â€œal-Kitabwal al-Qur'an: Qira'ah Muashirahâ€ by Syahrur. Linguistically, the verses were analyzed using syntagmatic and paradigmatic approach, and the special meanings in the Qur'an were integrated. The study revealed that the different terms in al-Kitab al-Qur'an, al-Dhikr, al-Furqan provide no basis for an argument and Â synonymous in the Quran is still debated. Â Synonymous is denied by Syahrur, but scholars rejecting the synonymous, only distinguish the properties contained in the words where the meaning remains the same. Â Quran can not be understood in the relative terms, as relative and dynamic in space and times.Â Â Â